The Kushnameh : the Persian epic of Kush the Tusked - Īrānshāh ibn Abī al-Khayr, active 11th century (University of California Press, 2022)
"The great Persian epic known as the Kushnameh follows the entangled lives of Kush the Tusked--a monstrous antihero with tusks and ears like an elephant, descended from the evil emperor Zahhak--and Abtin, the exiled grandson of the last true Persian emperor. Abandoned at birth in the forests of China and raised by Abtin, Kush grows into a powerful and devious warrior. Kush and his foes scheme and wage war across a global stage that reaches from Spain and Africa to China and Korea. In between epic battles and magnificent feasts, there are disturbing, sometimes realistic portrayals of abuse and oppression, and philosophical speculation about nature and nurture, and the origins of civilization. A fantastical adventure story stretching across the known world and a literary classic of unparalleled richness, this important work of medieval Persian literature is a valuable source for understanding the history of racism and constructions of race, and the flows of lore and legend from the Central Asian Silk Road and the Sahara to the sea-routes of the Indian Ocean and the Mediterranean. The Kushnameh is a treasure trove of Islamic and Pre-Islamic Persian cultural history and a striking contemporary document of the 'global middle ages,' now available to English-speaking readers for the first time"--